Application of Tarkhineh Fermented Product to Produce Potato Chips With Strong Probiotic Properties, High Shelf-Life, and Desirable Sensory Characteristics - Kiani, Amir; Nami, Yousef; Hedayati, Shahab; Elieh Ali Komi, Daniel; Goudarzi, Farjam; Haghshenas, Babak (Frontiers in Microbiology, 2021)
The application of Tarkhineh texture to protect probiotics in potato chips has been investigated as the main goal in this paper. In this study, the probiotic assessments, morphological characteristics, sensory evaluation, and survival rates of the covered probiotic cells with Tarkhineh in potato chips during storage time were assessed. Based on results, T34 isolated from traditional Tarkhineh as a safe strain had a high tolerance to low pH and bile salt conditions, displayed acceptable anti-pathogenic activities, and also showed desirable antibiotic susceptibility. Two types of Tarkhineh formulations (plain Tarkhineh and turmeric Tarkhineh) were applied using a simple spraying method for covering T34 cells in potato chips. All formulations showed elliptical to spherical (480-770 µm) shape probiotic drops. Storage stability results revealed that T34 cells mixed with turmeric and plain Tarkhineh during 4 months of storage at 4 ºC displayed excellent protection abilities with about 3.70 and 2.85 log decreases in CFU/g respectively. Additionally, probiotic potato chips compared to non-probiotic and commercial potato chips, exhibited probiotic product criteria such as excellent quality and superior sensory properties during storage time. In conclusion, Tarkhineh showed high potential as a protective matrix for probiotic cells in potato chips.